Interharmonic mitigation of adjustable speed drives using an active DC-link capacitor - Soltani, H.; Loh, P.; Blaabjerg, F.; Zare, Firuz (2015)
© 2015 Korean Institute of Power Electronics. Current and voltage source Adjustable - Speed Drives (ASDs) exert distortion currents in the grid which may lead to some interharmonic components other than the characteristic harmonic components. The frequencies of the line current interharmonics, generated by these ASDs, depend on the motor operating frequency. As there is a growing discussion about the interharmonic effects on the grid and its limitation, the reduction and mitigation of these components is worthwhile especially when more drives are tied to the grid. This paper proposes a new dc-link active capacitor in order to reduce the drive input current interharmonic components. Although the proposed active device is only applied on a voltage source ASD with unbalance load, the concept is general and can also be applied on the multi-pulse thyristor based adjustable speed drives. The study clearly verifies the effectiveness of the proposed dc-link active compensator on the grid current interharmonics reduction.